Factors Affecting ERP System Effectiveness in Post-Implementation Stage Within Malaysian Manufacturing Companies - Shatat, Ahmad Saleh; Mohamed Udin, Zulkifli (Inderscience Enterprises Ltd., 2013)
Enterprise resource planning (ERP) system has become one of the main pre-requisites for many companies enabling them to compete in the local and global market, a price of entry to gain a competitive advantage in the global economy, and a backbone for e-business as well as for the whole supply chain. Many companies are still reluctant to implement ERP system and therefore they will not be able to join the supply chain of several global and local companies where ERP system has become a pre-requisite and a price of entry for the global economy. This study has investigated the impact of ERP system on supply chain performance with respect to top management support, employee involvement, and cultural fit in the context of Malaysian manufacturing companies that are using ERP system and this is to fill up the gap in post-implementation stage. The study found that employee involvement, top management support, and cultural fit partially affects positively and significantly the relationship between ERP system and supply chain performance